Investigating of deep reinforcement learning-based techniques for robotic manipulation - Lee, Eu Shane (Nanyang Technological University, 2022)
This project is a continuation of the earlier work on reinforcement learning. The project will investigate on reinforcement learning based techniques for high dimensional robotic manipulation tasks. From earlier work, 4 reinforcement learning algorithms were implemented and tested on high dimensional robotic manipulation tasks.